PENGGUNAAN APE MAGIC BOX DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK DI KOBER LIL AULAD - Mulyono, Nono; Santika, Dewi; Nurlatifah, Dila (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
The Magic Box is a tool designed for playing which has educational value and a variety of games that can be used to develop early childhood’s cognitive aspect. This study aims to determine the implementation of using Magic Box and the teacher’s success to improve the early childhoods’ cognitive ability through the use of Magic Box at Kober Lil Aulad. In this study, the researchers use a classroom action research (CAR) as a research method. The results of this study show that the implementation of using Magic Box in developing the early childhoods’ cognitive ability in Kober Lil Aulad is categorized very well. This is based on the average score of 75% in the cycle I, then increased to 86.25% in the cycle II. Furthermore, the teacher has succeeded to improve the early childhoods’ cognitive ability at Kober Lil Aulad, which achieve a score of 70% with good criteria. In conclusion, the use of Magic Box has a positive impact on improving the early childhoods’ cognitive ability at Kober Lil Aulad.